Pengembangan Video Pembelajaran Fun Learning Berbantuan Canva untuk Pemecahan Masalah Materi Segiempat - Audea Dea; Dwi Oktaviana; Yadi Ardiawan (Universitas Islam Jember, 2026)
This study aimed to develop Canva-assisted fun learning instructional videos to improve students' mathematical problem-solving skills on quadrilateral topics in Grade VII of MTs Mujahidin Pontianak. The study employed a Research and Development (R&D) method using the 4-D model, consisting of the define, design, and development stages. The research subjects included three media experts, three material experts, and 30 seventh-grade students for product testing. Data were collected through validation sheets, response questionnaires, and essay tests. The results indicated that the developed instructional video was feasible for learning. The product achieved a validity score of 95.65%, categorized as very valid. Practicality based on teacher and student responses reached 93.3%, categorized as very practical. Effectiveness based on students' test results reached 80%, categorized as effective. Therefore, the developed instructional video is valid, practical, and effective for mathematics learning. Keywords: learning video, fun learning, canva, problem-solving ability